The Antifibrosis Effects of Peroxisome Proliferator-Activated Receptor δ on Rat Corneal Wound Healing after Excimer Laser Keratectomy. (13th November 2014) - Gu, Yun; Li, Xuan; He, Tiangeng; Jiang, Zhixin; Hao, Peng; Tang, Xin
Abstract : Corneal stromal fibrosis characterized by myofibroblasts and abnormal extracellular matrix (ECM) is usually the result of inappropriate wound healing. The present study tested the hypothesis that the ligand activation of peroxisome proliferator-activated receptor (PPAR) δ had antifibrosis effects in a rat model of corneal damage. Adult Sprague-Dawley rats underwent bilateral phototherapeutic keratectomy (PTK). The eyes were randomized into four groups: PBS, GW501516 (a selective agonist of PPAR δ ), GSK3787 (a selective antagonist of PPAR δ ), or GW501516 combined with GSK3787. The agents were subconjunctivally administered twice a week until sacrifice. The cellular aspects of corneal wound healing were evaluated with in vivo confocal imaging and postmortem histology. A myofibroblast marker ( α -smooth muscle actin) and ECM production (fibronectin, collagen type III and collagen type I) were examined by immunohistochemistry and RT-PCR. At the early stages of wound healing, GW501516 inhibited reepithelialization and promoted angiogenesis. During the remodeling phase of wound healing, GW501516 attenuated the activation and proliferation of keratocytes, which could be reversed by GSK3787. GW501516 decreased transdifferentiation from keratocytes into myofibroblasts, ECM synthesis, and corneal haze. These results demonstrate that GW501516 controls corneal fibrosis and suggest that PPAR δ may potentially serve as a therapeutic target for treating corneal scars.